Nuclear physics for cultural heritage - Azaiez, Faiçal; MacGregor, Douglas; Macková, Anna; Nyberg, Johan; Piasetzky, Eli (Nuclear Physics Division of the European Physical Society, 2016)
Nuclear physics applications in medicine and energy are well known and widely reported. Less well known are the many important nuclear and related techniques used for the study, characterization, assessment and preservation of cultural heritage. There has been enormous progress in this field in recent years and the current review aims to provide the public with a popular and accessible account of this work. The Nuclear Physics Division of the EPS represents scientists from all branches of nuclear physics across Europe. One of its aims is the dissemination of knowledge about nuclear physics and its applications. This review is led by Division board member Anna Macková, Head of the Tandetron Laboratory at the Nuclear Physics Institute of the Czech Academy of Sciences, and the review committee includes four other members of the nuclear physics board interested in this area: Faiçal Azaiez, Johan Nyberg, Eli Piasetzky and Douglas MacGregor. To create a truly authoritative account, the Scientific Editors have invited contributions from leading experts across Europe, and this publication is the combined result of their work. The review is extensively illustrated with important discoveries and examples from archaeology, pre-history, history, geography, culture, religion and curation, which underline the breadth and importance of this field. The large number of groups and laboratories working in the study and preservation of cultural heritage across Europe indicate the enormous effort and importance attached by society to this activity
Keywords: Nuclear; Datation; Radiographie en archéologie; radiocarbon dating; Radiocarbon dating; Radiography in archaeology; SCIENCE / Physics / Nuclear; Cultural property -- Radiography; Electronic book; Electronic books